Android-Based AR Game for Teaching Division to Students with Mild Intellectual Disabilities - Sri Rahayu; Widayati; Ken Sabardiman Soetjipto; Siska Setyaningsih; Ahmad Bachtiar Zen (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to develop innovative learning media in the form of Android-based educational games with Augmented Reality (AR) technology to help students with intellectual disabilities (mild mental retardation) in public high schools in the DKI Jakarta area understand the basic concepts of division in mathematics. The limitations of conventional learning media and the lack of teacher knowledge in digital technology development are the background of this study. The approach used is Research and Development (R&D) with the Multimedia Development Life Cycle (MDLC) method, which includes the stages of conceptualisation, design, material collection, creation, testing, and distribution. The developed application was validated by media experts, material experts, as well as teachers and students through questionnaires, showing positive responses to the material, design, and language aspects. A total of 56.5% strongly agreed that the application improved their understanding of division, and 60.9% strongly appreciated the design features. The language used in the application was perceived as easy to understand, reflected in 96.7% positive responses. Moreover, the application encouraged active participation (100%), increased learning interest (100%), and contributed positively to classroom activities (95.3%). The test results concluded that this application is effective in attracting students' interest and improving their understanding of the concept of division, and can be an innovative solution in inclusive education based on the principles of Gender Equity and Social Inclusion (GESI). This learning media is expected to expand access, improve the quality of learning, and support equal education rights for children with mild intellectual disabilities.